Predicting transitions between longitudinal classes of post-traumatic stress disorder, adjustment disorder and well-being during the COVID-19 pandemic: protocol of a latent transition model in a general Dutch sample. Issue 1 (7th January 2022) - Lenferink, Lonneke; Mouthaan, Joanne; Fritz, Anna M; Soydas, Suzan; Eidhof, Marloes; van Hoof, Marie-José; Groen, Simon; Mooren, Trudy
Abstract : Background: A growing body of literature shows profound effects of the COVID-19 pandemic on mental health, among which increased rates of post-traumatic stress disorder (PTSD) and adjustment disorder (AD). However, current research efforts have largely been unilateral, focusing on psychopathology and not including well-being, and are dominated by examining average psychopathology levels or on disorder absence/presence, thereby ignoring individual differences in mental health. Knowledge on individual differences, as depicted by latent subgroups, in the full spectrum of mental health may provide valuable insights in how individuals transition between health states and factors that predict transitioning from resilient to symptomatic classes. Our aim is to (1) identify longitudinal classes (ie, subgroups of individuals) based on indicators of PTSD, AD and well-being in response to the pandemic and (2) examine predictors of transitioning between these subgroups. Methods and analysis: We will conduct a three-wave longitudinal online survey study of n≥2000 adults from the general Dutch population. The first measurement occasion takes place 6 months after the start of the pandemic, followed by two follow-up measurements with 6 months of intervals. Latent transition analysis will be used for data analysis. Ethics and dissemination: Ethical approval has been obtained from four Dutch universities. Longitudinal study designs are vital to monitor mental health (and predictors thereof) in the pandemic to develop preventive and curative mental health interventions. This study is carried out by researchers who are board members of the Dutch Society for Traumatic Stress Studies and is part of a pan-European study (initiated by the European Society for Traumatic Stress Studies) examining the impact of the pandemic in 11 countries. Results will be published in peer-reviewed journals and disseminated at conferences, via newsletters, and media appearance among (psychotrauma) professionals and the general public.